2002
DOI: 10.1097/00000539-200206000-00030
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of OP-1206 α-CD on Walking Dysfunction in the Rat Neuropathic Intermittent Claudication Model

Abstract: Intermittent motor dysfunction is a clinical symptom associated with partial spinal compression. The present study provides evidence that oral treatment with the prostaglandin E1 analog (OP-1206 alpha-CD) is effective in improving motor dysfunction and spinal cord blood flow in rats with spinal compression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 18 publications
0
16
0
Order By: Relevance
“…So far, some experimental studies of the effect of lipo-PGE1 on blood flow in normal [68,70] and compressed [76][77][78][79][80] nerve roots have reported an increase in flow, but none have examined the effect of lipo-PGE1 on compressed sections with apparently Wallerian degeneration after nerve root compression. After investigating the changes of nerve root blood flow caused by bolus intravenous injection of Lipo-PGE1, Toribatake et al [68] reported a 59% increase of blood flow at a dose of 0.1 mg/kg, while Murakami et al [70] reported a 37.8% increase at a dose of 0.15 mg/kg.…”
mentioning
confidence: 99%
“…So far, some experimental studies of the effect of lipo-PGE1 on blood flow in normal [68,70] and compressed [76][77][78][79][80] nerve roots have reported an increase in flow, but none have examined the effect of lipo-PGE1 on compressed sections with apparently Wallerian degeneration after nerve root compression. After investigating the changes of nerve root blood flow caused by bolus intravenous injection of Lipo-PGE1, Toribatake et al [68] reported a 59% increase of blood flow at a dose of 0.1 mg/kg, while Murakami et al [70] reported a 37.8% increase at a dose of 0.15 mg/kg.…”
mentioning
confidence: 99%
“…However, the extent of compression applied to the nerve root and its duration were both insufficient, and the response was not compared with tissue changes of the nerve root after compression. [23][24][25][26] In the present study, intravenous injection of lipo-PGE 1 significantly increased intraradicular blood flow in the control group without nerve root compression, but the increase of blood flow observed in the compressed region of the nerve root exhibiting Wallerian degeneration was transient and not sustained. It is therefore concluded that lipo-PGE 1 has less effect on severely damaged nerve roots than it does on normal nerve roots.…”
Section: Discussionmentioning
confidence: 70%
“…However, investigations in the clinical setting have shown that lipo-PGE 1 is effective in some patients but not in others, [13][14][15][16][17][18][19][20][21][22] although the reason for this is unclear. So far, some experimental studies of the effect of lipo-PGE 1 on blood flow in normal 15,17 and compressed [23][24][25][26] nerve roots have reported an increase in flow, but none have examined the effect of lipo-PGE 1 on compressed sections with apparently Wallerian degeneration after nerve root compression. The aim of the present study was to measure changes in intraradicular blood flow after intravenous injection of lipo-PGE 1 using a laser Doppler flow meter in control and nerve root compression model.…”
mentioning
confidence: 99%
“…Limaprost is an oral prostaglandin E1 derivative that exhibits diverse effects, including inhibition of platelet aggregation, improvement of erythrocyte deformability, and inhibition of reactive oxygen production, in addition to having a potent vasodilatory action [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Increased blood flow in nerve tissue compressed by the narrowed spinal canal is the main mechanism of action of limaprost [5,6], and this improves leg pain, leg numbness, and intermittent claudication in patients with LSS [4].…”
Section: Introductionmentioning
confidence: 99%